The Sorcerer's Apprentice - Rodda, Emily (Sydney Scholastic Press, 2004)
The Raven Hill gang is hired to clean up the local magic shop. Soon Tom and the gang are involved in a dangerous game that tests their wits and courage. Ages 9+
Keywords: Detective and mystery stories -- Magic -- Brigands and robbers